Estudos de Durabilidade Frente ao Ataque Ácido de Compósitos Portland-Polímero para Cimentação de Poços de Petróleo - Nóbrega, Ana Cecília Vieira da (2008)
Portland-polymers composites are promising candidates to be used as cementing material in Northeastern oil wells of Brazil containing heavy oils submitted to steam injection. In this way, it is necessary to evaluate its degradation in the commonly acidizind agents. In addition, to identify how aggressive are the different hostile environments it is an important contribution on the decision of the acidic systems to be used in. It was investigated the performance of the Portland-polymer composites using powdered polyurethane, aqueous polyurethane, rubber tire residues and a biopolymer, those were reinforced with polished carbon steel SAE 1045 to make the electrochemical measurements. HCl 15,0 %, HCl 6,0 % + HF 1,5 % (soft mud acid), HCl 12,0 % + HF 3,0 % (regular mud acid) and HAc 10 % + HF 1,5 % were used as degrading environment and electrolytes. The more aggressive acid solution to the plain Portland hardened cement paste was the regular mud acid, that showed loss of weight around 23.0 %, followed by the soft mud acid, the showed 11.0 %, 15.0 % HCl with 7,0 % and, at last the 10.0 % HAc plus HF 1.5 % with just 1.0 %. The powdered polyurethane-composite and the aqueous polyurethane one showed larger durability, with reduction around 87.0 % on the loss of weight in regular mud acid. The acid attack is superficial and it occurs as an action layer, where the degraded layer is responsible for the decrease on the kinetic of the degrading process. This behavior can be seen mainly on the Portland- aqueous polyurethane composite, because the degraded layer is impregnated with chemically modified polymer. The fact of the acid attack does not have influence on the compressive strength or fratography of the samples, in a general way, confirms that theory. The mechanism of the efficiency of the Portland-polymers composites subjected to acid attack is due to decreased porosity and permeability related with the plain Portland paste, minor quantity of Ca+2, element preferentially leached to the acidic solution, wave effect and to substitute part of the degrading bulk for the polymeric one. The electrolyte HAc 10 % + HF 1,5 % was the least aggressive one to the external corrosion of the casing, showing open circuit potentials around +250 mV compared to -130 mV to the simulated pore solution to the first 24 hours immersion. This behavior has been performed for two months at least. Similar corrosion rates were showed between both of the electrolytes, around 0.01 μA.cm-2. Total impedance values, insipient arcs and big polarization resistance capacitive arcs on the Nyquist plots, indicating passivity process, confirm its efficiency. In this way, Portlandpolymers composites are possible solutions to be succeed applied to oilwell cementing concomitant submitted to steam injection and acidizing operation and the HAc 10,0 % + HF 1,5 % is the less aggressive solution to the external corrosion of the casing